The SIP security fallacy. Issue 6 (June 2016) - German, Paul
Abstract : There is no such thing as static security – all security products become vulnerable over time as the threat landscape evolves. Any 'deploy once, update infrequently or never' security solution is inherently flawed. Which is why every switched-on organisation routinely updates its anti-virus and anti-malware solutions, hardens its infrastructure and updates its policies. So why is SIP security still based upon a one-off implementation of a Session Border Controller (SBC)?